2004
DOI: 10.1002/cbf.1101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of therapeutic and toxic doses of levamisole on thyroid hormones and some biochemical parameters in sheep

Abstract: This study was carried out to establish the effects of therapeutic and toxic doses of levamisole on thyroid hormone levels and some biochemical parameters in sheep. Twelve Akkaraman ewes were used. Levamisole was given orally at doses of 7.5 mg kg(-1) (group 1) and 40 mg kg(-1) (group 2) to the animals. Blood samples were taken from the jugular vein at 2, 4, 8, 24, 48, 96 and 144 h after the administrations. Serum thyroid hormones and some biochemical parameters were determined on these samples. When compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Concerning the thyroid hormones, the higher T 4 and T 3 concentrations in blood plasma of administrated groups were mainly related to direct impact of treatments on increasing thyroid stimulating hormones (TSH) and immune potentiating impact on thyroid metabolism, particularly with Se-Met+LEV together. These findings are in accordance with Gunter et al (2003) and Atessahin et al (2004). Beckett (1992) reported that about 80% of T 3 in blood plasma is produced in the kidney, liver and muscle and all these tissues contain the Se-depending enzyme type IDI.…”
Section: Blood Constituents Of Damssupporting
confidence: 90%
See 3 more Smart Citations
“…Concerning the thyroid hormones, the higher T 4 and T 3 concentrations in blood plasma of administrated groups were mainly related to direct impact of treatments on increasing thyroid stimulating hormones (TSH) and immune potentiating impact on thyroid metabolism, particularly with Se-Met+LEV together. These findings are in accordance with Gunter et al (2003) and Atessahin et al (2004). Beckett (1992) reported that about 80% of T 3 in blood plasma is produced in the kidney, liver and muscle and all these tissues contain the Se-depending enzyme type IDI.…”
Section: Blood Constituents Of Damssupporting
confidence: 90%
“…Moreover, Schrauzer and Surai (2009) indicated that selenomethionine is the only naturally occurring Se compound that is significantly incorporated into body proteins. Atessahin et al (2004) reported that administration of levamisole significantly enhanced the serum albumin and reduced the total cholesterol in ewes.…”
Section: Blood Constituents Of Calvesmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports of levamisole intoxication are, in their entirety (Atessahin et al, 2004;Babish et al, 1990;Rather et al, 2020;Dar et al, 2020), the result of drug overdose.…”
Section: Epgmentioning
confidence: 99%